Construções teórico práticas sobre a leitura e a escrita iniciais: um estudo com professoras alfabetizadoras - Santos, Eliane Aparecida Galvão dos (2007)
This research is inserted in the line of Formação, Saberes e Desenvolvimento Profissional (Formation, knowledge and Professional Development) from Programa de Pós-Graduação em Educação da UFSM. The study had as objective to investigate what are the conceptions from the teachers of literacy about the initial reading and writing and to understand the repercussion of those conceptions in their daily practices. The studies of Ferreiro (1993, 1999, 2001, 2005), Bolzan (2001, 2002) Vygotsky (2003), Nóvoa (1991,1992, 1997), among others, were used as theoretic contribution for the development of this investigation. The research was carried out at a institution of Education of the State of Rio Grande do Sul located at outskirts of Santa Maria. The participants are four teachers who developed their pedagogical work with students of first and second grade of Ensino Fundamental. The investigation was developed through a narrative qualitative study and based on the speaking/voices from the teachers of literacy. The choice of that approach was done because we believe that it is through of choices and the interactive process that the teachers have the opportunity to present their beliefs, their thoughts and they discuss and reflect about the reality which they are living. The search of the findings was done through of semi structured interviews and of the observations of the classes. During that process it was discussed and reflected what the teachers of literacy believe that is relevant for carrying out a work of reading and writing in their classes and from that we analyzed what the repercussion from those conception in their pedagogical practices. The findings of the research emphasized that the pedagogical practices of the teachers were directly related with the conception of literacy that they constructed during their academic and professional experience at school. Those theoretic and practical constructions had a direct repercussion at the manner as they developed their pedagogical activities. Thus, the findings point out that even the teachers having the traditional concept of learning the moment that they are living is a non- stabilization moment between the necessity of implementation of the new forms of performance at class and the knowledge acquired by them during their formation. The availability and the interest of the teachers in order to go deeper into theoretical studies that come to contributed for the pedagogical practice based on social interaction and preview knowledge from the students show that the investment at continued formation of the teacher from of the reflection process is essential to assumption of the relation of theory and practice every day at school and, consequently, the transformation of the initial reading and writing practices incorporated into literacy